Cysteine Dioxygenase 1 Mediates Erastin-Induced Ferroptosis in Human Gastric Cancer Cells - Hao, Shihui; Yu, Jiang; He, Wanming; Huang, Qiong; Zhao, Yang; Liang, Bishan; Zhang, Shuyi; Wen, Zhaowei; Dong, Shumin; Rao, Jinjun; Liao, Wangjun; Shi, Min (Neoplasia (New York, N.Y.), 2017)
BACKGROUND: Ferroptosis is a recently discovered form of iron-dependent nonapoptotic cell death. It is characterized by loss of the activity of the lipid repair enzyme, glutathione peroxidase 4 (GPX4), and accumulation of lethal reactive lipid oxygen species. However, we still know relatively little about ferroptosis and its molecular mechanism in gastric cancer (GC) cells. Here, we demonstrate that erastin, a classic inducer of ferroptosis, induces this form of cell death in GC cells and that cysteine dioxygenase 1 (CDO1) plays an important role in this process. METHODS: We performed quantitative real-time polymerase chain reaction, Western blotting, cell viability assay, reactive oxygen species (ROS) assay, glutathione assay, lipid peroxidation assay, RNAi and gene transfection, immunofluorescent staining, dual-luciferase reporter assay, transmission electron microscopy, and chromatin immunoprecipitation assay to study the regulation of ferroptosis in GC cells. Mouse xenograft assay was used to figure out the mechanism in vivo. RESULTS: Silencing CDO1 inhibited erastin-induced ferroptosis in GC cells both in vitro and in vivo. Suppression of CDO1 restored cellular GSH levels, prevented ROS generation, and reduced malondialdehyde, one of the end products of lipid peroxidation. In addition, silencing COO1 maintained mitochondrial morphologic stability in erastin-treated cells. Mechanistically, c-Myb transcriptionally regulated CDO1, and inhibition of CDO1 expression upregulated GPX4 expression. CONCLUSIONS: Our findings give a better understanding of ferroptosis and its molecular mechanism in GC cells, gaining insight into ferroptosis-mediated cancer treatment.